KEGALAUAN IDENTITAS: DILEMA HUBUNGAN MUSLIMIN DAN HINDU DI BALI - Siti Raudhatul Jannah (Ulumuna, 2012)
Abstract: The relationship between Hindu and Muslim communities in Bali has been recorded in the long trajectory of history of both communities. As a human relationship, the relationship sometimes becomes strength, but at the other hand, as the adherents of different religions, it becomes challenge to them. The challenge is how the Muslim community in Bali can respect and honor Hindu religious traditions, and how the Hindu community can do the same to the Muslim community. The article aims to elaborate further about it. The author presents three cases as examples of how Muslims practice their religion in Bali context. Tolerance is the key word how to mingle in the social, moral principles, religious law and social ethics. Abstrak: Hubungan antara komunitas Hindu dan Muslim di Bali telah terekam dalam lintasan panjang sejarah dua komunitas itu. Sebagai sebuah hubungan antar manusia, ia kadang-kadang menjadi suatu kekuatan bagi keduanya, tetapi sisi lain, sebagai pengikut agama yang berbeda, ia menjadi suatu tantangan. Tantangan itu adalah bagaimana komunitas Muslim di Bali bisa menghormati tradisi keagamaan Hindu dan bagaimana pula komunitas Hindu menghormati komunitas Muslim. Artikel bertujuan untuk mengelaborasi lebih jauh tentang hal tersebut. Penulis memaparkan tiga contoh kasus tentang bagaimana Muslim menjalankan agama mereka dalam konteks kehidupan di Bali. Toleransi adalah kata kunci bagaimana membaur dalam kehidupan sosial, prinsip moral, hukum agama, dan etika sosial.